HOW TO APPROACH THE PROBLEM OF LOW BACK PAIN: AN OVERVIEW - Nasser, Munir J. (Medknow Publications & Media Pvt Ltd, 2005)
The management of patients with low back pain (LBP) problems by primary care physicians or even spine specialists differ significantly and little is known about treatment strategy. This review is to present the clinical profile and to assess the most common treatment modalities of patients with low-back pain in order to improve the clinical judgment of the treating physician. Data were obtained from a midline literature search of articles in English. A manual revision of original articles was done and demonstrative figures from patients at our institute were added. LBP is an extremely common problem. It is characterized by attacks, remissions and exacerbations. It is best managed by a multidisciplinary team. Primary coordination of treatment may depend on the patient's need and the awareness of the treating physician of the importance of history and physical examinations. The following suggested protocol may help to identify red flags that denote more serious conditions.